PELAKSANAAN REDISTRIBUSI TANAH OBYEK LANDREFORM DI KABUPATEN TABANAN - Sari, Charina; Wyasa Putra, Ida Bagus (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014)
Land reform is a mean to improve farmers' lives standard thus the main goals to achieve include those of economy, social-politic, and mental-psychology. To execute the goals the government has conducted land reform in the narrow sense, one of them includes the activity of land redistribution project. Land redistribution is the division of the lands owned by the state and have already stated as objects of the land reform given to the farmers fulfilling the requirements of governmental regulation No. 224 Year 1961. It is tended to improve the state of social economy of the people by holding the land distribution fairly.
Keywords: Landreform, Land Redistribution